2014
DOI: 10.1177/0743558414556343
|View full text |Cite
|
Sign up to set email alerts
|

Fortifying Leisure

Abstract: This study examined family leisure patterns and meanings of family leisure from the perspective of adolescents living in the Mukono District of Uganda. Sixty-eight secondary students were interviewed. Results indicate Ugandan adolescent definitions of leisure reflect leisure as free time and leisure as a means to an end. Students mentioned three primary family leisure outcomes (enjoyment/fun, personal development, and family development) that point toward a core theme. Fortifying describes the importance Ugand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(55 reference statements)
0
1
1
Order By: Relevance
“…Furthermore, this research also found that family involvement in leisure activities was not significantly correlated with the dimensions of personal growth. These results do not align with several studies that explain that family involvement in leisure activities can support individual development (McGovern et al, 2014;Pomfret & Varley, 2019). Personal growth is a condition where a person knows himself and utilizes his potential and abilities (Ryff, 2013).…”
Section: Variablecontrasting
confidence: 87%
“…Furthermore, this research also found that family involvement in leisure activities was not significantly correlated with the dimensions of personal growth. These results do not align with several studies that explain that family involvement in leisure activities can support individual development (McGovern et al, 2014;Pomfret & Varley, 2019). Personal growth is a condition where a person knows himself and utilizes his potential and abilities (Ryff, 2013).…”
Section: Variablecontrasting
confidence: 87%
“…The final article in the Special Section, on adolescents’ views of family leisure in Uganda, by McGovern and colleagues (2015), provides insights into adolescents’ lives in an African country. It also provides an example of successful collaboration between Western and non-Western researchers.…”
Section: The Special Section: Expanding Research On Cultural Variatiomentioning
confidence: 99%